Deciphering and engineering the polyunsaturated fatty acid synthase pathway from eukaryotic microorganisms - Guo, Pengfei; Dong, Liang; Wang, Fangzhong; Chen, Lei; Zhang, Weiwen (Frontiers in Bioengineering and Biotechnology, 2022)
Polyunsaturated fatty acids (PUFAs) are important nutrients that play important roles in human health. In eukaryotes, PUFAs can be de novo synthesized through two independent biosynthetic pathways: the desaturase/elongase pathway and the PUFA synthase pathway. Among them, PUFAs synthesized through the PUFA synthase pathway typically have few byproducts and require fewer reduction equivalents. In the past two decades, numerous studies have been carried out to identify, analyze and engineer PUFA synthases from eukaryotes. These studies showed both similarities and differences between the eukaryotic PUFA synthase pathways and those well studied in prokaryotes. For example, eukaryotic PUFA synthases contain the same domain types as those in prokaryotic PUFA synthases, but the number and arrangement of several domains are different; the basic functions of same-type domains are similar, but the properties and catalytic activities of these domains are somewhat different. To further utilize the PUFA synthase pathway in microbial cell factories and improve the productivity of PUFAs, many challenges still need to be addressed, such as incompletely elucidated PUFA synthesis mechanisms and the difficult genetic manipulation of eukaryotic hosts. In this review, we provide an updated introduction to the eukaryotic PUFA synthase pathway, summarize the functions of domains and propose the possible mechanisms of the PUFA synthesis process, and then provide future research directions to further elucidate and engineer the eukaryotic PUFA synthase pathway for the maximal benefits of humans.